Measuring Vulnerability for Small Areas - Sawyer, Chase (International Journal of Population Data Science, 2024)
This presentation will show how the Census Bureau used multiple data sources and small area methodologies to create the Community Resilience Estimates, a measure of social vulnerability to disasters.